2016
DOI: 10.4322/0104-4931.ctoao0575
|View full text |Cite
|
Sign up to set email alerts
|

Perfil De Trabalhadores Com Doenças Da Coluna Vertebral Atendidos Em Um Serviço De Saúde

Abstract: showed that 27.9% (n=19) presented also soft tissue injuries (M60 to M79), 3.2% (n=09) mental disorders, and 70.9% (n=39) were in absence from work. Conclusion: The most affected age was in the productive phase and more than half of the subjects were in absence from work situation, some subjects with other clinical diagnosis, reinforcing the need of interdisciplinary interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…Mais da metade dos trabalhadores deste estudo tinham idade entre 30 e 49 anos (52,4%). Sujeitos em fase de vida produtiva com distúrbios osteomusculares foram encontrados em outros estudos (VALENÇA et al, 2016;DOSEA et al, 2015;FREITAS et al,2015). Em relação à escolaridade, e diferente desse estudo, e no contexto brasileiro no período entre 2007 a 2012, a maioria dos trabalhadores notificados possuía o ensino médio completo (48,3%), embora tenha sido expressiva a quantidade de trabalhadores com apenas ensino fundamental (41,5%) (MELO et al, 2015).…”
Section: Discussionunclassified
“…Mais da metade dos trabalhadores deste estudo tinham idade entre 30 e 49 anos (52,4%). Sujeitos em fase de vida produtiva com distúrbios osteomusculares foram encontrados em outros estudos (VALENÇA et al, 2016;DOSEA et al, 2015;FREITAS et al,2015). Em relação à escolaridade, e diferente desse estudo, e no contexto brasileiro no período entre 2007 a 2012, a maioria dos trabalhadores notificados possuía o ensino médio completo (48,3%), embora tenha sido expressiva a quantidade de trabalhadores com apenas ensino fundamental (41,5%) (MELO et al, 2015).…”
Section: Discussionunclassified
“…Seria importante para o serviço e usuário obter um diagnóstico clínico para o tratamento, como também um diagnóstico funcional e fisioterapêutico, porém nem sempre os sujeitos retornavam ao serviço com os exames clínicos solicitados, talvez por se "perderem" na rede de serviços, indicando dificuldades na intersetorialidade entre os serviços de saúde, havendo a necessidade de maiores investigações a este respeito. Em outro estudo realizado no mesmo serviço, a lombalgia também foi prevalente entre os trabalhadores e 8,8% dos prontuários analisados (n=431) também não constavam um diagnóstico clínico estabelecido 12 .…”
Section: Discussionunclassified
“…In a study (continues) Table 4. Continuation with seamstresses from Minas Gerais, Brazil, it was observed that 53.6% presented indicative symptoms of common mental disorders that could probably be turned into depression 12 . As for the medicines used by seamstresses, the main were contraceptives, drugs that act on the cardiovascular system and kidneys and drugs that act on the central and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that these workers are often submitted to high levels of stress due to overload and pressure for productivity and meeting deadlines, causing mental disorders such as depression, which is one of the biggest reasons of work leave of these women 12,14 . Most workers showed musculoskeletal symptoms in the last 12 months and seven days before the interview.…”
Section: Discussionmentioning
confidence: 99%